FINANCIAL CONDITION MODERATED THE EFFECTIVENESS OF AUDIT COMMITTEETOREDUCE EARNINGSMANAGEMENT - Michella Maria Virgine Prayogo; Yie Ke Feliana; Aurelia Carina Christanti Sutanto (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
Some cases of financial fraud invite inquiries about the effectiveness of corporategovernance mechanism in financial distress companies. This study empiricallyexamines whether the financial distress moderate the impact of corporate governancemechanism to earnings management. The sample of this study is manufacturingcompanies listed at Indonesia Stock Exchange for period 2010 -2012. Discretionaryaccruals are used as a proxy for earnings management, while financially distressed andnon-distressed firms are identified based on Altman Z-score test. Corporate governancemechanism is measured by four characteristics of the audit committee, i.e. size (totalnumber of audit committee members), independence (audit committee composition),activity(frequency of audit committee meeting), and expertise (the number of auditcommittee have finance or accounting background).This study finds that (1) financialdistress does not moderate the impact of total members of audit committee to earningsmanagement; (2) financial distress does not moderate the impact of frequency of auditcommittee meeting to earnings management; (3) financial distress does not moderatethe impact of audit committee composition to earnings management; (4)financialdistress moderates the impact of audit committee finance/accounting knowledge toearnings management. These results suggestthat the effectiveness corporate governanceis low, and finance/accounting literacy of audit committee should be alert.Beberapa kasus manipulasi keuangan pada perusahaan yang mengalami kesulitankeuangan mengundang pertanyaan terkait efektifitas mekanisme tata kelola perusahaan.Penelitian ini secara empiris menguji apakah kondisi kesulitan keuangan dapatmemoderasi pengaruh mekanisme tata kelola perusahaan terhadap manajemen laba.Sampel dari penelitian ini adalah perusahaan sektor manufaktur yang terdaftar di BursaEfek Indonesia periode 2010-2012.Discretionary accruals digunakan sebagai proksiuntuk manajemen laba, sedangkan kondisi kesulitan keuangan diidentifikasimenggunakan uji Altman Z-score. Mekanisme tata kelola perusahaan diukur dengan 4karakteristik komite audit, yaitu ukuran (jumlah anggota komite audit), independensi(komposisi komite audit), aktivitas (frekuensi pertemuan komite audit), dan keahlian(jumlah anggota komite audit yang memiliki latar belakang keuangan atau akuntansi).Penelitian ini menemukan bahwa (1) kondisi kesulitan keuangan tidak memoderasipengaruh jumlah anggota komite audit terhadap manajemen laba; (2) kondisi kesulitankeuangan tidak memoderasi pengaruh frekuensi pertemuan komite audit terhadapmanajemen laba; (3) kondisi kesulitan keuangan tidak memoderasi pengaruh komposisikomite audit terhadap manajemen laba; (4) kondisi kesulitan keuangan memoderasi pengaruh jumlah anggota komite audit yang memiliki latar belakang keuangan atauakuntansi terhadap manajemen laba. Hasil ini menunjukkan bahwa efektifitas tatakelola perusahaan masih rendah dan anggota komite audit yang memiliki latar belakangkeuangan atau akuntansi harus mewaspadainya.